Digital Amnesia in Indonesia Generation Z on Instagram Advertisement Information Absorption - Jeanne Prasetyo; Lady Joanne Tjahyana; Felicia Goenawan (Institute of Research and Community Outreach - Petra Christian University, 2024)
Digital Amnesia is the experience of forgetting information that you trust a digital device to store and remember for you. The researcher uses four indicators of digital amnesia: remember without looking up, emotional impact of losing data or access to data, behavior related to internet searches, and install IT securities on devices. This research will find out the level of digital amnesia in Indonesia Generation Z on Instagram advertisement information absorption. The research is using quantitative descriptive approach and online survey method. The questionnaire was distributed to 100 respondents using purposive sampling method. The theories used by the researcher include the S-O-R (Stimulus-Organism-Response) theory, Marketing Public Relations theory, Digital Amnesia theory and Consumer Behavior theory. The research shows that Generation Z experiences digital amnesia the most when they see Story Ads, and the least when they see Reels Ads. This is supported by the data showing that Generation Z is categorized as having high levels in all four indicators (remember without looking up, emotional impact of losing data, behavior related to internet searches, and install IT security on devices).